Short-term changes of permafrost degradation triggered by anthropogenic impacts and climatic events in Western Siberia 2010-2013. - Noerling, Caroline; Dvornikov, Yury; Morgenstern, Anne; Bartsch, Annett; Khomutov, Artem V; Heim, Birgit (PANGAEA, 2017)
The data set presents results from geospatial analyses of a region in Central Yamal, Western Siberia, which was affected by the construction of the Bovanenkovo railway line and by high Retrogressive Thaw Slumps (RTS) occurrence in consequence of the extremely warm and wet year 2012. A change detection was performed using high resolution optical satellite images from 2010 (GeoEye-1) and 2013 (QuickBird). The preprocessing of the satellite data (orthorectification and atmospheric correction) was performed by and is described in Dvornikov et al., 2016. The degree of disturbance change from 2010 and 2013 around the railway line was classified into three major disturbance levels - low, medium and high, based on the width of disturbance and magnitude of change over the course of three years. A kernel density raster file illustrates RTS distribution. The highest disturbance along the railway can be observed, where the RTS activity is the highest in 2013.
Permafrost disturbance in Central Yamal along the Bovanenkovo railway line and thermokarst lakes, link to files in different formats
Keywords: AWI_PerDyn; File content; File format; File name; File size; MULT; Permafrost Research (Periglacial Dynamics) @ AWI; Uniform resource locator/link to file; Vaskiny_Dachi_Area; Vaskiny Dachi, Yamal Peninsula, West Siberia, Russian Federation